Bayesian methods in health economics: formulating input uncertainty 5 - O'Hagan, Anthony (Henry Stewart Talks, 2009)
How to express uncertainty about model inputs, The analysis of the vaccine model exemplifies the basic approaches, Accounting for data gaps, Recognizing correlation between uncertain inputs, Evaluating uncertainty in utilities
Reviewed at 2022/03/30